Prostate magnetic resonance imaging and the value of experience: An intrareader variability study - Thomas Whish-Wilson; Jo-Lynn Tan; William Cross; Lih-Ming Wong; Tom Sutherland (Asian Journal of Urology)
Objective: To measure the intraobserver concordance of an experienced genitourinary radiologist reporting of multiparametric magnetic resonance imaging of the prostate (mpMRIp) scans over time. Methods: An experienced genitourinary radiologist re-reported his original 100 consecutive mpMRIp scans using Prostate Imaging-Reporting and Data System version 2 (PI-RADS v2) after 5 years of further experience comprising >1000 scans. Intraobserver agreement was measured using Cohen's kappa. Sensitivity, specificity, negative predictive value (NPV), positive predictive value (PPV), and accuracy were calculated, and comparison of sensitivity was performed using McNemar's test. Results: Ninety-six mpMRIp scans were included in our final analysis. Of the 96 patients, 53 (55.2%) patients underwent subsequent biopsy (n=43) or prostatectomy (n=15), with 73 lesions targeted. Moderate agreement (Cohen's kappa 0.55) was seen in the number of lesions identified at initial reporting and on re-reading (81 vs. 39 total lesions; and 71 vs. 37 number of PI-RADS ≥3 lesions). For clinically significant prostate cancer, re-reading demonstrated an increase in specificity (from 43% to 89%) and PPV (from 62% to 87%), but a decrease in sensitivity (from 94% to 72%, p=0.01) and NPV (from 89% to 77%). Conclusion: The intraobserver agreement for a novice to experienced radiologist reporting mpMRIp using PI-RADS v2 is moderate. Reduced sensitivity is off-set by improved specificity and PPV, which validate mpMRIp as a gold standard for prebiopsy screening.